2014
DOI: 10.1007/s11948-014-9572-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Disclosure and Ethics Education on Perceptions of Financial Conflicts of Interest

Abstract: This study explored how disclosure of financial conflicts of interest (FCOI) influences naïve or "lay" individuals' perceptions of the ethicality of researcher conduct. On a between-subjects basis, participants read ten scenarios in which researchers disclosed or failed to disclose relevant financial conflicts of interest. Participants evaluated the extent to which each vignette represented a FCOI, its possible influence on researcher objectivity, and the ethics of the financial relationship. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a randomized trial using mailed financial disclosure letters to patients, nearly one in four patients reported that knowing financial disclosure increased their trust (2). Disclosures also significantly reduced individuals' perception of researchers' ethics, but only marginally affected perceptions of a researchers' objectivity (10). Disclosures appear at least sometimes to create a false sense of security, contrary to their intended purpose of increasing awareness for potential author bias.…”
Section: An Evidence-based Evaluation Of Disclosurementioning
confidence: 97%
“…In a randomized trial using mailed financial disclosure letters to patients, nearly one in four patients reported that knowing financial disclosure increased their trust (2). Disclosures also significantly reduced individuals' perception of researchers' ethics, but only marginally affected perceptions of a researchers' objectivity (10). Disclosures appear at least sometimes to create a false sense of security, contrary to their intended purpose of increasing awareness for potential author bias.…”
Section: An Evidence-based Evaluation Of Disclosurementioning
confidence: 97%
“…However, questions may arise as to whether this is ethical in a sense by not giving full disclosure. When failure to reveal potentially negative information could cause harm to the competition, then obviously an ethical conundrum is evident and integrity of the business could be damaged (Sacco et al 2014). However, within the context of the business deal, bluffing a weak hand is not considered unethical by remaining within legal parameters (Carr 1968).…”
Section: Bluffing a Robust Handmentioning
confidence: 99%
“…For readers, the presence of a disclosed conflict of interest may influence their response to information in unexpected ways, including increasing their trust or making them dismissive of the material [ 46 , 47 ]. However, in a recent study within a small group, it was found that the disclosure of a financial conflict of interest had little impact on a lay audience’s interpretation of research and helped to moderate the concerns of audiences with training in ethics [ 48 ].…”
Section: Introductionmentioning
confidence: 99%